Network Analyses of Maternal Pre- and Post-Partum Symptoms of Depression and Anxiety - Phua, Desiree Y.; Chen, Helen; Chong, Yap Seng; Gluckman, Peter D.; Broekman, Birit F. P.; Meaney, Michael J. (Frontiers in Psychiatry, 2020)
Background. Maternal mental health problems often develop prenatally and predict postpartum mental health. However, the circumstances before and following childbirth differ considerably. We currently lack an understanding of dynamic variation in the profiles of depressive and anxiety symptoms over the perinatal period. Methods. Depressive and anxiety symptoms were self-reported by 980 women at 26-weeks pregnancy and three months postpartum. The pre- and post-partum depressive-anxiety symptom networks were assessed for changes in structure, unique symptom-symptom interactions, central and bridging symptoms. Predictive values of central symptoms on offspring were assessed with different outcomes at birth and 24, 54, and 72 months old. Bridging symptoms between negative and positive mental health were also assessed. Results. Though the depressive-anxiety network structures were stable during and after pregnancy, the postpartum network was more strongly connected. There were also changes in symptom-symptom interactions and central symptoms. Central symptoms were associated with poorer birth and development outcomes for the child. Symptoms that bridged depressive and anxiety symptoms changed after pregnancy. Symptoms that bridged negative and positive mental health were also different pre- and post-natally. Conclusions. The differences between pre- and post-partum networks suggest that the presentation of maternal mental health problems varies over the peripartum period. This variation is not captured by traditional symptom scale scores. Interventions and public health policies should thus be tailored to specific pre- and post-partum symptom profiles.